Outcomes of multivessel vs culprit lesion‐only percutaneous coronary intervention in patients with acute myocardial infarction complicated by cardiogenic shock: Evidence from an updated meta‐analysis. Issue 1 (28th December 2018) - Kundu, Amartya; Sardar, Partha; Kakouros, Nikolaos; Malhotra, Rohit; Kolte, Dhaval; Feldman, Dmitriy N.; Abbott, JD; Fisher, Daniel Z.
Abstract: Objectives: This updated meta‐analysis evaluated outcomes with multi‐vessel (MV‐PCI) vs culprit lesion‐only percutaneous coronary intervention (CL‐PCI), in patients with acute myocardial infarction (AMI) complicated by cardiogenic shock (CS). Background: There is considerable debate regarding the optimal revascularization strategy in patients with AMI and CS, particularly regarding management of non‐culprit lesions. Methods: Databases were searched for studies comparing MV‐PCI and CL‐PCI in patients with AMI and CS. The primary outcome of interest was short‐term all‐cause mortality. Secondary outcomes included long‐term mortality, repeat revascularization and myocardial reinfarction. Safety outcomes were stroke, acute renal failure and major bleeding. Pooled odds ratios (OR) and 95% confidence intervals (CI) were estimated using random‐effects models. Results: Our meta‐analysis consisting of 14 studies (13 observational, 1 RCT) involving 8, 552 patients showed that in comparison to CL‐PCI, MV‐PCI was associated with similar short‐term mortality (OR 1.14; 95% CI 0.9–1.43), as well as similar long‐term mortality (OR 0.94; 95% CI 0.68–1.28). There was no significant difference in the risk of myocardial reinfarction (OR 1.19; 95% CI 0.76–1.86), or repeat revascularization (OR 0.79; 95% CI 0.41–1.55) between the two groups. Compared to CL‐PCI, MV‐PCI was associated with a similar risk of bleeding (OR 1.13; 95% CI 0.91–1.40) and stroke (OR 1.28; 95% CI 0.84–1.96), but a higher risk of developing renal failure (OR 1.32; 95% CI 1.05–1.65). Conclusions: Our meta‐analysis suggests that there is a higher risk of renal failure with no additional benefit in efficacy outcomes with MV‐PCI, compared to CL‐PCI in patients with AMI and CS.